Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $p<q$ be positive integers (with the allowance that $q$ may be $\infty$). How can we show that the sum of $L^p$ and $L^q$ is a Banach space under the norm $\|f\|=\inf\{\|g\|_p+\|h\|_q: g+h=f\}$?

Let $\{f_n\}$ be a sequence in $L^p+L^q$, such that $$\sum_{n=1}^\infty \|f_n\|<\infty.$$

We would like to conclude that this implies that $\sum_{n=1}^\infty f_n$ converges to something in $L^p+L^q$, at which point it follows that $L^p+L^q$ is complete by a basic theorem. We could easily do this if for each $f_i$ it were possible to express $f_i=g_i+h_i$, where $g_i\in L^p, h_i\in L^q$ and $\|f_i\|=\|g_i\|_p+\|h_i\|_q$. Though we know Cauchy sequences in $L^p$ converge, it is not clear that for a given $f$, all sequences (or some sequence) $\{g_n+h_n\}$ such that the $(\|g_n\|_p+\|h_n\|_q)\to \|f_n\|$ have the property that $\{g_n\},\{h_n\}$ converge in their respective spaces. It seems possible to imagine the sum converging without the summands converging in their respective spaces.

Any help would be much appreciated.

share|improve this question
add comment

2 Answers

up vote 2 down vote accepted

You want in fact to show the following result:

Let $(X_1,||\cdot||_1)$ and $(X_2,||\cdot||_2)$ two Banach spaces such that $X_i\subset V$ where $f$ is a vector space. We define $X=\{x_1+x_2,x_1\in X_1,x_2\in X_2\}$ endowed with the norm $||x||_X:=\inf\{||x_1||_1+||x_2||_2,x=x_1+x_2\}$. Then $(X,||\cdot||_X)$ is a Banach space.

To see that, take $\{x^{(n)}\}$ a Cauchy sequence in $X$. We can extract a subsequence, denoted $\{y^{(k)}\}$ such that $||y^{(k+1)}-y^{(k)}||_X\leq 2^{-k}$ for all $k$. Let $(y_1^{(k)}, y_2^{(k)})\in X_1\times X_2$ such that $||y^{(k+1)}-y^{(k)}||_X+2^{-k}\geq ||y_1^{(k)}||_{X_1}+||y_2^{(k)}||_{X_2}$ and $y^{(k+1)}-y^{(k)}=y_1^{(k)}+y_2^{(k)}$. Since $X_1$ and $X_2$ are Banach spaces we can define $y_1:=\sum_{k=0}^{+\infty}y_1^{(k)}$ and $y_2:=\sum_{k=0}^{+\infty}y_2^{(k)}$. We have $$y^{(n+1)}=y^{(0)}+\sum_{k=0}^ny^{(k+1)}-y^{(k)}+y^{(0)}=\sum_{k=1}^ny_1^{(k)}+\sum_{k=1}^ny_2^{(k)}+y^{(0)},$$ which shows that $y^{(n)}$ converges to $\sum_{k=0}^{+\infty}y_1^{(k)}+\sum_{k=0}^{+\infty}y_2^{(k)}+y^{(0)}$.

share|improve this answer
add comment

Hint: for each $n$, choose $g_n \in L^p$, $h_n \in L^q$ such that $f_n = g_n + h_n$ and $||g_n||_p + ||h_n||_q \le ||f_n|| + 2^{-n}$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.